Cost impact of self-measurement of blood glucose on complications of type 2 diabetes: the Spanish perspective - Neeser, Kurt; Weber, Christian (Diabetes technology & therapeutics, 2009)
Despite the increasing prevalence of type 2 diabetes, its financial burden on the Spanish healthcare system remains unclear. This study was conducted to determine the cost share of self-measurement of blood glucose (SMBG) by comparing the direct costs of reduced complications of diabetes in SMBG users versus nonusers in the Spanish statutory health insurance system. Matched-pair analysis was done of the average annual total direct cost of diabetes monitoring, treatment-related services, complications, and follow-up in the RetrOlective Study Self-Monitoring of Blood Glucose and Outcome in Patients with Type 2 Diabetes (ROSSO) study cohort, updated to 2008 from the year of occurrence or diagnosis of diabetes. In patients treated with oral antidiabetes drugs (OADs) only, total annual costs were euro1,934 in SMBG users and euro1,982 in nonusers. In those treated with OADs plus insulin, total annual costs were euro3,451 and euro4,167, respectively. By increasing the number of patients using SMBG, the Spanish statutory health insurance system might save several million Euros annually. The analysis showed that the promotion of SMBG in patients with type 2 diabetes is associated with considerable cost savings for the Spanish healthcare system.